2020
DOI: 10.1016/j.jhealeco.2020.102316
|View full text |Cite
|
Sign up to set email alerts
|

The winter choke: Coal-Fired heating, air pollution, and mortality in China

Abstract: If it is the author's pre-published version, changes introduced as a result of publishing processes such as copy-editing and formatting may not be reflected in this document. For a definitive version of this work, please refer to the published version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(92 citation statements)
references
References 48 publications
(33 reference statements)
1
81
0
Order By: Relevance
“…A large number of researches has confirmed the link between high levels of air pollutants and deteriorating health, in both developed countries ( Lavaine and Neidell, 2017 ; Deryugina et al, 2019 ) and developing countries ( Ebenstein et al, 2017 ; Fan et al, 2020 ). Here, we present a brief analysis on the health benefits from the air improvement during the lockdown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of researches has confirmed the link between high levels of air pollutants and deteriorating health, in both developed countries ( Lavaine and Neidell, 2017 ; Deryugina et al, 2019 ) and developing countries ( Ebenstein et al, 2017 ; Fan et al, 2020 ). Here, we present a brief analysis on the health benefits from the air improvement during the lockdown.…”
Section: Resultsmentioning
confidence: 99%
“…We used Web of Science, Google Scholar, Scopus, and other databases to identify academic articles and book chapters that meet these criteria, and it could be found that eligible articles in this field are not that rich. Finally, Fan et al (2020) who, through a Regression Discontinuity (RD) analysis, found that a 10-μg/m 3 increase in PM 2.5 resulted in a 2.2% increase in mortality rate; and He et al (2020) who proposed that this rate can reach over 3.25% through an estimation of the effect of straw burning on air pollution and health are chosen as two main references. We are assuming that the cause-specific coefficient ( RR ) in China is a representative one, thus 2.2%– 3.25% increase in mortality following a 10-μg/m 3 increase in PM 2.5 is applicable to the whole world.…”
Section: Resultsmentioning
confidence: 99%
“…If the haze control relies on such temporary regulations, it may worsen the environment in the long run (Shi, Guo, and Chen 2016). Some scholars also study the factors, such as the impact of straw burning, that cause air pollution in the short term (Balwinder-Singh et al 2019;He, Liu, and Zhou 2020) and the deterioration of air quality caused by winter heating in northern China (Chen et al 2013a;2017;Fan, He, and Zhou 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, two main references are chosen after the article selection. Specially, Fan et al ( 2020 ), in their empirical study based on a regression discontinuity (RD) analysis, found that a 10-μg/m 3 increase in PM 2.5 would lead to a 2.2% increase in mortality rate. The other one is He et al ( 2020b ), who indicated that this rate could reach over 3.25 percent based on an estimation of the effect of straw burning on air pollution and associated health problem in China.…”
Section: Resultsmentioning
confidence: 99%